Circuit modeling of an UWB patch antenna - Badjian M.H.; Chakrabarty C.K.; Devkumar S.; Hock G.C. (2023)
An Ultra wideband (UWB) patch antenna is analyzed in this paper. The design uses FR-4 substrate with dielectric constant of 4.9 and thickness of 1.6 mm. Circuit model of such antenna is developed under AWR Microwave Office environment. Obtained results from simulating the antenna in CST Microwave Studio are then compared with the results taken from the Circuit Model. 2008 IEEE.